The relationships between rugby union and health: a scoping review protocol. Issue 1 (24th August 2019) - Griffin, Steffan Arthur; Panagodage Perera, Nirmala Kanthi; Murray, Andrew; Hartley, Catherine; Brooks, John H M; Kemp, Simon P T; Stokes, Keith A
Abstract : Introduction: Rugby union is played by over eight million people across the world and is considered a form of moderate-to-vigorous physical activity. Consequently, playing rugby may confer health benefits; however, to date, the principal focus of research has been on associated injuries and potential detrimental long-term health sequelae. This protocol outlines the methods behind studying any potential associations between rugby union and both physical and mental health. Methods and analysis: Best practice methodological frameworks (Arksey and O'Malley, Levac et al and the Joanna Briggs Institute) and previously published scoping review protocols in sport informs the methodology of this protocol. This protocol enables us to map the key concepts and evidence available, summarise and share existing research ﬁndings, and identify research gaps in the current literature. A three-step search strategy will identify reviews, original research, and published and grey literature. An initial search will identify suitable search terms, followed by a search using keyword and index terms. Two reviewers will independently screen identiﬁed studies for final inclusion. Dissemination: When publishing the scoping review, we will map key concepts and evidence both numerically and thematically, as well as identify key research priorities for further studies. The review will subsequently be disseminated to stakeholder groups, practitioners and policymakers through a variety of peer-reviewed and non-peer-reviewed publications, conferences and via multimedia platforms.